ARTISTIC SYMBOLS AND IMAGES IN ALISHER NAVOI'S FRIENDS AND GHAZALS (Archive of Conferences, 2020)
Alisher Navoi is one of the great figures who had a great influence on the formation of the spiritual world of our people. Today, Navoi's works can be an important source of instilling in young people a sense of national pride, self-awareness, beauty and elegance. Indeed, the ideas embodied in the essence of the great artist's works, such as humanity, nationalism, justice, truth, maturity of faith, gratitude, patience, hope for the future, are important for the spiritual maturity of mankind in all ages. In addition, I think that the symbols and emblems and images in Navoi's works are created through a very beautiful poetic skill, and it is necessary to convey the essence of their content to students through bright evidence